Examining the impact of tourism on local communities in Wae Rebo tourism village NTT using the doxey index - Ramdhan Kurniawan; Asep Parantika (Institute of Computer Science (IOCS), 2023)
Tourism development in many places has proven to not only have positive impacts, but also negative impacts on tourist destinations, including local communities. To reduce the negative impacts of tourism activities on tourist destinations, it is highly dependent on planned and sustainable tourism development. Therefore, it is necessary to assess the impact of tourism activities currently felt by local communities in tourist destinations to determine the corrective measures needed to achieve planned tourism development. This research aims to examine at which stage tourism development has been felt by the local community of Wae Rebo - NTT using the Doxey Irritation Index theory. This research uses a descriptive quantitative-qualitative mixed method. Primary data was collected by conducting questionnaires to 44 heads of families of the Wae Rebo community, and interviewing several stakeholders such as village heads, tribal heads, heads of tourism offices, related NGOs. Secondary data was obtained from various literature and data publications that support the theme and object of research. This applied research will be conducted for 6 months. It is expected that by expressing the opinions of local people about the impact of tourism development in Wae Rebo village - NTT. It can be known the stages of irritation that are currently felt, as well as the impact on social, cultural, economic and environmental in the village of Wae Rebo Tourism - NTT.